Hubungan Peran Orang Tua Dan Keterpaparan Media Terhadap Pengetahuan Tentang HIV/AIDS Pada Siswa Siswi SMP Muhammadiyah Cilegon Tahun 2023 : Hubungan Peran Orang Tua Dan Keterpaparan Media Terhadap Pengetahuan Tentang HIV/AIDS Pada Siswa Siswi SMP Muhammadiyah Cilegon Tahun 2023 - Avicenna Agustin, Evi; Sri Susanti; Rif’atul Mahmmudah (Prodi DIII Kebidanan La Tansa Mashiro, 2024)
Adolescence is a transitional period from childhood to adulthood, involving biological, psychological, and socio-cultural changes. The World Health Organization (WHO) defines adolescence as a phase marked by the development of secondary sexual characteristics, sexual and reproductive maturation, the attainment of adult mental identity, and the transition from socio-economic dependence to independence. In Indonesia, the definition of adolescence varies across institutions, with the National Population and Family Planning Board (BKKBN) categorizing it as ages 10–24 years, while the Ministry of Health defines it as ages 10–19 years. Reproductive health issues among adolescents have become a growing concern, particularly due to the rise in sexually transmitted infections (STIs) and HIV/AIDS cases. The study aims to examine the factors associated with adolescents' knowledge of HIV/AIDS at SMP Muhammadiyah Cilegon in 2023. This research employs an analytical survey method with a cross-sectional approach, observing both independent and dependent variables simultaneously. The study was conducted in June 2023, involving a total sampling of 180 students. Data were collected using questionnaires assessing knowledge of HIV/AIDS, media exposure, and parental roles. The findings indicate that 67.8% of respondents had low media exposure, 48.3% had poor parental involvement, and 58.3% had insufficient knowledge of HIV/AIDS. Statistical analysis revealed a significant relationship between media exposure and knowledge of HIV/AIDS (p-value = 0.000; OR = 4.365). These results highlight the importance of increasing media exposure and parental involvement to enhance adolescents' understanding of HIV/AIDS. Strengthening reproductive health education through schools, family support, and reliable media sources is essential in preventing risky behaviors and promoting responsible adolescent sexual health.